Parental negligence: an inquiry towards the application of Section 17,31 and 33 of Child Act 2001 and Section 304A of Penal Code / Abd Rahim Ali, Nomadinar Ramly and Noor Mazrinie Mahmood - Ali, Abd Rahim; Ramly, Nomadinar; Mahmood, Noor Mazrinie
The title for our research is "Parental Negligence: The Application on Section 17, 31, 33 of Child Act 2001 and Section 304A of Penal Code". Therefore, this project paper contains the discussion on parental negligence as well as a comprehensive explanation as to the laws which govern this matter. The laws include Section 17, 31, 33 of Child Act 2001 and Section 304A of Penal Code. We are focusing on the application of these provisions in respect of parental negligence. In the first chapter of our research paper, we give a brief introduction about parental negligence. We also laid down our objectives that we need to accomplish in this research paper as well as method of research that we adopted in this research, Hence, we also include the significance of study, limitation of study and provisional plan of our research. In the second chapter, we provide the laws and the principles which govern matters in parental negligence. In the Chapter 3, we analysed common law cases, views by experts as well as mass media on parental negligence. Chapter 4 is the vital part of our research paper as we have made our own findings and conclusions of the laws on parental negligence based on all the information we gathered from this research. We also formulate several recommendations to solve the issue that arises on parental negligence. This research is hoped to be useful reference to the authorities in enforcing the laws against negligent parents.